Advanced Chemical Reactor Technologies for Biodiesel Production from Vegetable Oils - A Review - Luqman Buchori; Istadi Istadi; Purwanto Purwanto (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
Biodiesel is an alternative biofuel that can replace diesel oil without requiring modifications to the engine and advantageously produces cleaner emissions. Biodiesel can be produced through transesterification process between oil or fat and alcohol to form esters and glycerol. The transesterification can be carried out with or without a catalyst. The catalyzed production of biodiesel can be performed by using homogeneous, heterogeneous and enzyme. Meanwhile, non-catalytic transesterification with supercritical alcohol provides a new way of producing biodiesel. Microwave and ultrasound assisted transesterification significantly can reduce reaction time as well as improve product yields. Another process, a plasma technology is promising for biodiesel synthesis from vegetable oils due to very short reaction time, no soap formation and no glycerol as a by-product. This paper reviews briefly the technologies on transesterification reaction for biodiesel production using homogeneous, heterogeneous, and enzyme catalysts, as well as advanced methods (supercritical, microwave, ultrasonic, and plasma technology). Advantages and disadvantages of each method were described comprehensively.